CLINICAL CASE OF RUSSIAN THROMBOLYTIC AGENT FORTELYZIN® USE IN PATIENTS WITH ACUTE CORONARY ARTERY DISEASE - K. A. Kireev; A. V. Krasnopeev; S. V. Utkina (Рациональная фармакотерапия в кардиологии)
One of the three clinical examples of hospital thrombolysis using Russian thrombolytic agent recombinant protein comprising an amino acid sequence of staphylokinase is described. The trial was held in Chelyabinsk Regional Vascular Centre of specialized medical care for patients with acute coronary syndromes. Each of the three patients had similar reasons for systemic intravenous thrombolysis: hospitalization with ST-segment elevation myocardial infarction, unavailability of coronary interventions due to the X-ray operating room occupancy, high need for the reperfusion therapy in the setting of significant acute myocardial ischemia. In all the cases the pharmacologic reperfusion with recombinant protein comprising an amino acid sequence of staphylokinase was successful, hereafter percutaneous coronary interventions were performed. There were no complications registered.